Ethical Eating in the Postsocialist and Socialist World - Yuson Jung, Jakob A. Klein, and Melissa L. Caldwell (University of California Press, 2014)
In spring 2013, alternative food activists and their supporters took to the streets around the world to protest against GM (genetically modifi ed) foods and Monsanto, arguably one of the most visible symbols behind the spread of genetically modifi ed seeds. Organizers claimed that more than two million people throughout the world, but primarily in Western capitalist countries in North America and Western Europe, participated in the demonstrations, although the fi gure was not necessarily verifi ed by independent media. In market socialist (or â€œreform socialist,â€ Hann and Hart 2011: 137â€“39) and postsocialist countries, the response seemed to be much more muted, with few details in local or international media about any noticeable anti-Monsanto activity. In Russia, a rally in Moscow, a city with a population of approximately fi fteen million, drew only fi fty people, mainly to protest Russiaâ€™s recent membership in the World Trade Organization, which requires Russia to relax its existing regulations against the importation of genetically modifi ed products. Similarly in Bulgaria, which has the most stringent law against GM farming in the European Union (it is virtually impossible to plant GMO (genetically modifi ed organism) seeds in Bulgarian soil), only dozens of activists and citizens joined in the global protest in the two cities of Sofi a and Veliko Turnovo, demanding better GMO labeling for imported food. In China, where Monsanto has a formal joint venture with the state, although some citizens have expressed concerns about the importation of GMO productsâ€”what one Chinese natural sciences professor described as an impending â€œbiological invasionâ€â€”there is no evidence of any noticeable awareness of or participation in these larger global protests.Yet this relative silence from market socialist and postsocialist citizens should not be interpreted as a lack of concern over the ethical dimensions of the contemporary food system. Rather, market socialist and postsocialist citizens have been extremely vocal and visible in questioning the ethics behind food production and consumption and demanding high standards for â€œeating right,â€ whether that is in terms of diet and nutrition, farming practices, animal welfare, production and distribution systems, or social obligations to reduce hunger and poverty.